Gender differences in the use of psychiatric outpatient specialist services in Tromsø, Norway are dependent on age: a population-based cross-sectional survey. Issue 1 (June 2015) - Hansen, Anne; Høye, Anne
Abstract Background Overall, men are less likely than women to seek health care services for mental health problems, but differences between genders in higher age groups are equivocal. The aim of the current study was to investigate the association between gender and the use of psychiatric outpatient specialist services in Norway, both in a general population and in a subpopulation with self-reported anxiety and/or depression. Methods Using questionnaires from 12, 982 participants (30–87 years) in the cross-sectional sixth Tromsø Study (2007-8) we estimated proportions reporting anxiety/depression, and proportions using psychiatric outpatient specialist services in a year. By logistic regressions we studied the association between gender and the use of psychiatric outpatient specialist services. Analyses were adjusted for age, marital status, income, education, self-reported degree of anxiety/depression, and GP visits last year. Analyses were also performed for genders separately. Results Anxiety/depression was reported by 21.5 % of women and 12.3 % of men in the general population. Visits to psychiatric outpatient services during one year were reported by 4.6 % of women and 3.3 % of men. The general population's probability of a visit was significantly lower among men compared to women in ages 30–49 years (odds ratio [OR] 0.58, confidence interval [CI] 0.39–0.84, p -value [p ] = 0.004), whereas men used services slightly more than women in ages 50 years and over (OR 1.36, CI 1.00–1.83, p  = 0.047). Among those with anxiety/depression 13.5 % of women and 10.5 % of men visited psychiatric outpatient services in a year. We found no statistically significant gender differences in the use of services in this subgroup. Other factors associated with services use in women with anxiety/depression were higher education, more severe anxiety/depression, and GP visits the last year, whereas in men only a more severe anxiety/depression was associated with psychiatric outpatient visits. Overall, the use of services decreased with higher age. Conclusions Most people with self-reported anxiety/depression did not visit specialist outpatient clinics. This applies in particular to men aged 30–49 years, older individuals, and individuals with lower education. Gender differences in the use of services in the general population were dependent on age, whereas in the subgroup with anxiety/depression gender differences were not confirmed.